2015
DOI: 10.4103/2230-8210.159056
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in solitary thyroid nodule: A clinicoradiopathological evaluation

Abstract: Background:Thyroid nodules are common. They can be either benign or malignant. Solitary thyroid nodules (STN) have a high likelihood of being malignant. They should be characterized properly for optimum management.Materials and Methods:In this study, we have analyzed our departmental data over a period of 5 years. All the patients who presented to the outpatient department with a clinically detected STN were included in the study group. Our approach was individualized. Preoperative ultrasonography (USG) and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 19 publications
3
28
1
2
Order By: Relevance
“…Out of four malignancies that were confirmed by histopathology, two cases were correctly reported by FNAC and the remaining two cases were reported as suspicious. A study done by Jena et al 11 reported that fine-needle aspiration cytology done before the surgery on 146 patients, the findings were nodular goitre in 62 (42.5%), follicular neoplasm in 55 (37.7%), papillary carcinoma in 25 (17.1%), Hashimoto thyroiditis in two (1.4%), toxic nodule in one (0.7%) and medullary carcinoma in one (0.7%) patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of four malignancies that were confirmed by histopathology, two cases were correctly reported by FNAC and the remaining two cases were reported as suspicious. A study done by Jena et al 11 reported that fine-needle aspiration cytology done before the surgery on 146 patients, the findings were nodular goitre in 62 (42.5%), follicular neoplasm in 55 (37.7%), papillary carcinoma in 25 (17.1%), Hashimoto thyroiditis in two (1.4%), toxic nodule in one (0.7%) and medullary carcinoma in one (0.7%) patient.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The occurrence of malignancy is more in solitary thyroid nodules compared to multinodular goitre. 10,11 This increase in incidence is due to identification through the use of ultrasound examinations and the emphasis on early detection of cancer over the past three decades. 12 The occurrence of solitary thyroid nodule is a common entity.…”
mentioning
confidence: 99%
“…In a study of 300 patients, 46.2% of solitary thyroid nodules were malignant compared to 22.5% of MNG (7,8). However, this was not the case in several other studies, which reported no difference in cancer prevalence between patients with solitary nodules and those with MNG (9,10,16).…”
Section: Discussionmentioning
confidence: 88%
“…FNAC is considered the most reliable method for the detection of malignancy in midline neck masses prior to surgery [6]. Since a majority of lesions are cystic in nature, FNAC of the mural nodule under ultrasound guidance can improve the diagnostic accuracy by reducing the false-negative results [2,7,8].…”
Section: Discussionmentioning
confidence: 99%